Historical Matrix of Transfuguism. Between Freedom and Anomie in Political Institutionality - Delgado-Guembes, César (2006)
This article analyzes the emergence and evolution of transfuguism, as well as its structure and characteristics, from a legal perspective. The author argues that it is crucial to recognize the foundations and elements of this phenomenon. Although it is not possible to assume an illicit or criminal nature of this figure, it can generate states of anomie within the framework of political institutionality. The author suggests that a defector's desire to change political parties is influenced not only by personal factors, but also by the political environment and relationships within the new political group. Therefore, to prevent the anomie that comes with political party switching, it is suggested that citizens and political leaders take a deliberate stance against the culture of self-interest and individual gain, and instead prioritize the common good and civic responsibility.